CONSTRUCTION OF TRUST AND RISK IN SHOPPING DECISION-MAKING ON TIKTOK SHOP: A DIGITAL ETHNOGRAPHY STUDY - A’iffatan Dina Khunafa; Anita Sumelvia Dewi (SOSIOEDUKASI, 2025)
This study examines how trust and risk perception shape shopping decisions on TikTok Shop, a growing form of live streaming-based social commerce in Indonesia. Using a qualitative digital ethnography approach, it explores users’ social and emotional experiences through digital observation, in-depth interviews, and documentation of online interactions between hosts and young consumers in East Java. Findings reveal that trust emerges from social interaction, visual cues, and social validation. Communicative, transparent, and responsive hosts enhance credibility, while high-quality visuals reinforce authenticity and professionalism. Comments and testimonials (e-WOM) serve as collective validation, whereas negative experiences heighten perceived risk and caution. From the sellers’ perspective, offering discounts, showcasing testimonials, and maintaining honesty and consistency foster trust and loyalty. Theoretically, this study expands understanding of trust and risk in social commerce by emphasizing social and symbolic dimensions often overlooked by quantitative approaches. Practically, it guides TikTok Shop practitioners in building authentic, empathetic communication and encourages consumers to strengthen digital literacy in evaluating seller credibility. Overall, trust and risk in digital shopping emerge from dynamic interactions among humans, algorithms, and social representations within virtual marketplaces.